Some Spectral Properties of p-Laplacian Diffusion Boundary Value Problem on Time Scales - Gulsen, Tuba; Yilmaz, Emrah; Kayali, Meltem (E D P Sciences, 2018)
In this paper, we consider p-Laplacian type Diffusion boundary value problem on an arbitrary time scale. We generalize some spectral properties of p-Laplacian Diffusion problem to an arbitrary time scale. Moreover, we prove Picone's identity for this problem.
3rd International Conference on Computational Mathematics and Engineering Sciences (CMES) -- MAY 04-06, 2018 -- Final Int Univ, Girne, CYPRUS
Keywords: Multiple Positive Solutions; Dynamic Equations; Oscillation; Existence; Theorems; Identity